Chatter prediction for the peripheral milling of thin-walled workpieces with curved surfaces. (October 2016) - Yang, Yun; Zhang, Wei-Hong; Ma, Ying-Chao; Wan, Min
Abstract: Workpiece dynamics is the dominant factor which should be taken into consideration in chatter prediction of peripheral milling of thin-walled workpieces. Usually, material removal, tool position and varying dynamic displacements of the workpiece along the tool axis influence the workpiece dynamics. However, these three aspects were not considered simultaneously in the existing researches. This paper comprehensively investigates the effect of varying workpiece dynamics on the stability in peripheral milling of thin-walled workpieces with curved surfaces. A new dynamic model of tool and workpiece system is proposed to consider the dynamic behavior of tool and workpiece as well as the influences of engagement and tool feed direction. Interaction between tool and thin-walled workpiece is modeled at discrete nodes along the axial depth of cut. An efficient method based on structural dynamic modification scheme is developed to characterize the effect of material removal upon the in-process workpiece dynamics. This is done by only performing modal analysis on the FEM model of initial workpiece, while mode shapes and natural frequencies of the in-process workpiece can be calculated without re-building and re-meshing the instant FEM model at each tool position. The proposed model and method are verified by the milling process of two thin-walled workpieces concerning a plate and a workpiece with curved surface. Comparisons of numerical and experimental results show that chatter can be accurately predicted for the peripheral milling of thin-walled workpieces. Abstract : Highlights: A new dynamic model is proposed for peripheral milling of thin-walled workpieces. Influence of varying workpiece dynamics on stability of milling processes is considered. Effects of engagement and tool feed direction are considered when milling curved surfaces. An efficient method is presented to calculate varying workpiece dynamics. The model is verified by milling a plate and a workpiece with curved surface.